Is it worth using low-cost glass ionomer cements for occlusal ART restorations in primary molars? 2-year survival and cost analysis of a Randomized clinical trial - Olegário da Costa, Isabel (My University, 2020)
Objective: To evaluate the 2-year survival rate and the cost-effectiveness of Atraumatic Restorative Treatment (ART) using three different glass ionomer cements (GICs) for restoring occlusal dentin caries lesions in primary molars. Methods: One hundred and fifty (150) 4-8-year-old children were selected, randomly allocated and treated in school tables according to the restorative material: Fuji IX Gold Label (GC Corp), Vitro Molar (nova DFL) and Maxxion R (FGM), the latter two being low-cost brands. Materials and professionals' costs were considered to analyse baseline total cost, and from this the cumulative cost of each treatment was calculated. Restoration assessments were performed after 2, 6, 12 and 24 months by an independent calibrated examiner. Restoration survival was estimated using Kaplan-Meier survival analysis and Cox regression was used to test association with clinical factors. Bootstrap regression (1,000 replications) compared material´s cost over time and Monte-Carlo simulation was used to build cost-effectiveness scatter plots. Results: The overall survival rate of occlusal ART restorations after 2 years was 53% (Fuji IX = 72.7%; Vitro Molar = 46.5%; Maxxion R = 39.6%). Restorations performed with Vitro Molar and Maxxion R were more likely to fail when compared to Fuji IX. At baseline, Fuji IX was the more expensive option (p < 0.001), however, considering the simulation of accumulated cost caused by failures until 2-year evaluation, no difference was found between the groups. Conclusions: After 2 years' follow up, restorations performed with Fuji IX proved to be superior in terms of survival, with a similar overall cost, when compared to low-cost glass ionomers cements (Vitro Molar and Maxxion R).
PUBLISHED
Keywords: Restoration survival; Primary teeth; Glass ionomer cement; Atraumatic restorative treatment; Cost-effectiveness; Dental material; Dentine caries; Nanoscience & Materials